2014
DOI: 10.1590/s1415-43662014000100002
|View full text |Cite
|
Sign up to set email alerts
|

Mudas de oiticica irrigadas com águas salinas no solo com biofertilizante bovino e potássio

Abstract: Um experimento foi conduzido entre março e junho de 2012 no Centro de Ciências Agrárias da UFPB, Areia, PB, para avaliar o crescimento inicial de plantas de oiticica (Licania rigida Benth), pela altura, diâmetro caulinar, área foliar, teor de clorofila total, biomassa das raízes e da parte aérea de plantas em função da salinidade da água, biofertilizante bovino e potássio no solo. Os tratamentos foram arranjados em delineamento inteiramente casualizado, com seis repetições, em esquema fatorial 5 x 2 x 2, corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 14 publications
(14 reference statements)
2
6
0
4
Order By: Relevance
“…In the soil with chemically enriched bovine biofertilizer, root growth increased linearly from 30.40 to 45.84 cm between plants irrigated with water of 0.5 and 4.0 dS m -1 , representing a gain of 50.8%. Similar behavior was observed for root growth in oiticica (Licania rigida Benth) seedlings irrigated with saline waters (DINIZ NETO et al, 2014). The biofertilizer, through its contribution of humic substances, promoted improvements in physical attributes of the soil, mainly in structure and porosity, which resulted in higher root growth under saline conditions (ALENCAR et al, 2018).…”
Section: Contentssupporting
confidence: 57%
See 1 more Smart Citation
“…In the soil with chemically enriched bovine biofertilizer, root growth increased linearly from 30.40 to 45.84 cm between plants irrigated with water of 0.5 and 4.0 dS m -1 , representing a gain of 50.8%. Similar behavior was observed for root growth in oiticica (Licania rigida Benth) seedlings irrigated with saline waters (DINIZ NETO et al, 2014). The biofertilizer, through its contribution of humic substances, promoted improvements in physical attributes of the soil, mainly in structure and porosity, which resulted in higher root growth under saline conditions (ALENCAR et al, 2018).…”
Section: Contentssupporting
confidence: 57%
“…One approach is the adoption of technologies to allow the use of brackish water in agriculture, without great losses in the quality of seedlings and crop yield. In this context, the bovine biofertilizer Vairo promotes greater root and aerial tissue growth, and greater formation of biomass, in comparison to plants without this organic input, during the formation of seedlings of several nonfruit and fruit species (DINIZ NETO et al, 2014;OLIVEIRA et al, 2017;LIMA NETO et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The other biofertilizers (quail, mixed, bovine, and crab) alleviated the salt stress for this variable. Diniz Neto et al (2014) also pointed out that the use of organic inputs as a way to mitigate the effects of salts on plants aims to increase the content of humic substances in the soil as organic matter. Souza et al (2019) found higher RDM in broad bean plants under saline stress and fertilization with bovine and caprine biofertilizer.…”
Section: De Acordo Commentioning
confidence: 99%
“…Quanto a MSR, apenas o biofertilizante ovino foi superior estatisticamente quando irrigado com água de baixa salinidade, enquanto para os demais biofertilizantes (codorna, misto, bovino e caranguejo) atenuaram o estresse salino para essa variável. Diniz Neto et al (2014), destacam ainda que utilização de insumos orgânicos como forma de atenuar os efeitos dos sais às plantas, visa incrementar o teor de substâncias húmicas no solo como matéria orgânica. Souza et al (2019), constataram maior MSR em plantas de fava sob estresse salino e adubação com biofertilizante bovino e caprino.…”
Section: De Acordo Comunclassified
“…Uma alternativa utilizada para minimizar os efeitos dos sais sobre o solo e as plantas, é o uso de matéria orgânica no solo, estimulando a redução do potencial osmótico, contribuindo para a absorção de água e, atenuando o dano provocado pela salinização às plantas (DINIZ NETO et al, 2014;FREIRE et al, 2015). No entanto, ainda são escassos trabalhos com ênfase no uso de matéria orgânica como atenuante da salinidade, evidenciando assim a necessidade de pesquisas que resultem em tecnologias viáveis para os produtores; e que possam minimizar os efeitos nocivos do excesso de sais nas plantas, já que é quase obrigatória, em regiões semiáridas, a utilização de águas salinas na agricultura (FREIRE et al, 2016).…”
unclassified